Utilizing the Senior Companion Program as a platform for a culturally informed caregiver intervention: Results from a mixed methods pilot study. (January 2021) - Fields, Noelle L; Xu, Ling; Richardson, Virginia E; Parekh, Rupal; Ivey, Dorothea; Calhoun, Melanie
To address the need for accessible, affordable, and sustainable Alzheimer's disease and related dementia caregiver interventions with minority populations, we developed the Senior Companion Program Plus, a three-phase pilot study that used a mixed methods experimental design. The intent was to determine if participation in a lay provider, peer-led psychoeducational intervention designed for African American Alzheimer's disease and related dementia caregivers ( N  = 16) improved caregiver burden and/or stress, coping skills, and social support. Focus groups with Senior Companions informed the intervention design. Quantitative results indicated that caregivers experienced improvement in their overall level of social support and well-being in meeting basic needs. Qualitative findings suggested that caregivers experienced improvement in their knowledge about the disease, experienced increased coping with Alzheimer's disease and related dementia caregiving, and reported benefits of using a lay provider model. Overall, the data suggest that the Senior Companion Program Plus is a promising intervention for African American Alzheimer's disease and related dementia caregivers.